IDENTIFIKASI JENIS SEMUT FAMILI FORMICIDAE DI KAWASAN TAMAN WISATA ALAM PANTAI PANJANG PULAU BAAI KOTA BENGKULU - Supriati, Rochmah; Sari, Winarti Purnama; Dianty, Nevee (Universitas Bengkulu, 2019)
The existence of insects is very abundant and has an important role in the ecosystem. In addition to a very important function in the ecosystem, ants are used as bioindicators in changing the habitat of an area and seeing changes occur in the environment. Ants are commonly found in a variety of habitats, in addition to terrestrial areas ants are found in coastal areas because there are habitats that allow the presence of ants in the form of mangrove vegetation and ecologically, ant nests are scattered from mangrove forests and trees on the coast. This research was conducted on 10 February - 10 March 2016 in the TWA area of Pantai Panjang, Pulau Baai Bengkulu. Use the roaming or xploration method. Each location point to set a trap (pitfall). When installing pitfalls (pitfall) is done at 09.00-11.00 and 14.00-15.00 WIB, by installing ten trap traps (pitfall) for three days. From the results in the field found 10 types of ants from the Order Hymenoptera Family Formicidae. 8 species constitute members of the Subfamily Formicinae including; A.gracilipes, P. longicornis, C. carnelius, Oecophylla sp, P. carbonaria, C. rufipes, Camponotus sp, P. jerdon, two other members of the Dolichoderinae Subfamily; T. melanocephalum, D. thoracicus.